Mechanism of liquid unloading by single flowing plunger lift in gas wells. (22nd January 2023) - Tan, Bo; Liu, Xingliang; Liu, Yi; Chang, Yongfeng; Tian, Wei; Jia, Youliang; Han, Guoqing; Liang, Xingyuan
Abstract: The plunger lift is one of the main methods to release liquid loading in gas wells. Due to the leakage in the process of moving for plunger, the efficiency of liquid unloading is decreased. In recent years, the single flowing plunger was invented and has been used in many gas fields. However, the mechanism of enhanced liquid unloading is still unclear. In this paper, a full-size visible plunger lift equipment was built to study the process of single flowing plunger lift (SFPL) and normal plunger lift (NPL). Moreover, a transient model was built to simulate SFPL and NPL in different situation. Results show that the SFPL can prevent the liquid from dropping, decrease the bottom-hole pressure, and enhance gas production. The SFPL performs well in a certain range, and the SFPL would be out of operation first. A plate has been built to help engineers optimize the SFPL. The paper helps clear the situation of SFPL and provides the theoretical basis for researchers. Highlights: A full-size visualized plunger lift equipment and a transient numerical model were built. The mechanism of liquid unloading for the single flowing plunger was revealed. Applied range of single flowing plunger was cleared.